2012
DOI: 10.1682/jrrd.2011.11.0218
|View full text |Cite
|
Sign up to set email alerts
|

Does a waist-worn ActiGraph accelerometer quantify community ambulation in persons with multiple sclerosis?

Abstract: Abstract-Accelerometry has been recognized as a method of objectively measuring community ambulation in persons with multiple sclerosis (MS). However, the assumption that walking itself serves as a major contributor to the accelerometer signal has yet to be tested. This study examined the assumption that community-based walking is a primary contributor to accelerometer output in MS. Ambulatory persons (5 males/17 females; 13 without aid/9 with aid) with MS wore a triaxial accelerometer (ActiGraph GT3X, Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Activity counts by such wearable activity monitors have been reported to be associated with disability status, and walking impairment in PwMS [ 12 , 13 ]. There have also been several investigations describing the accuracy of wearable activity monitors for counting steps in populations with gait impairment, including PwMS [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activity counts by such wearable activity monitors have been reported to be associated with disability status, and walking impairment in PwMS [ 12 , 13 ]. There have also been several investigations describing the accuracy of wearable activity monitors for counting steps in populations with gait impairment, including PwMS [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accelerometer was sampled at 30 Hz and values were expressed as number of counts per minute. Participants were instructed to wear the accelerometer on an elastic belt around the waist (i.e., near to the center of displacement of body mass) located above the hip at the non-dominant side [ 19 , 26 ], to wear it for a 7-day period (including a weekend), and to wear it for the whole day from getting out of bed in the morning until getting into bed in the evening. These instructions were summarized in a memo and given to participants.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerometry has been studied to be an objective method to examine community ambulation in pwMS [18]. Actigraph models from the GT3X series are often used accelerometers in studies on community walking of pwMS and have been found to be appropriate tools in this population [19,20]. In this study, the ActiGraph model wGT3X-BT was used.…”
Section: Actigraph Wgt3x-bt and Data Processingmentioning
confidence: 99%